Refining the psychometric properties of the Trinity Student Profile - A self-report measure of occupational performance difficulties within the student role in higher education. - Lombard, Kim (Trinity College Dublin. School of Medicine. Discipline of Occupational Therapy, 2024)
Background: The Trinity Student Profile (TSP) is a self-report measure of occupational performance difficulties within the university student role and is based on the Person-Environment-Occupation Model. The tool was developed in response to the increasing numbers of students with disabilities and mental health difficulties in university in Ireland and Classical Test Theory methodology was used to facilitate its development and piloting. The tool required further rigorous validation, and there is an increasing call for the use of person-centred measurement models such as Rasch analysis methodology to validate tools. This research aimed to refine the psychometric properties of the TSP. Methodology: A two-stage embedded design approach was used. Stage One aimed to refine the psychometric properties of the `Identifying Needs? section using Rasch analysis. Data from 667 TSP files from the disability services in Trinity College Dublin and University College Dublin was collected retrospectively and analysed using Rasch analysis. Stage Two aimed to affirm the face validity and clinical utility of the refined tool in practice. Occupational therapists from three universities engaged in an initial focus group to discuss experiences of using the 2014 version of the tool and were trained in using the refined tool. A follow-up focus group was held after trialling use of the refined tool in practice and the resulting qualitative data was analysed using thematic analysis. Results: The Rasch analysis in Stage One predominantly focused on the 6-point `Difficulty? scale used for 74-items across three item-sets (i.e., `Person? N=30; `Environment? N=20; `Occupation? N=24). The `Difficulty? scale demonstrated stronger psychometric properties as a combined item-set of occupational performance difficulties. Using this combined item-set, the 6-point scale was collapsed to a 4-point scale and 20 redundant items were removed. The 54-item 4-point scale demonstrated strong reliability, separation, and unidimensionality. An item difficulty hierarchy and paper-and-pencil keyform were developed to be used in practice. Preliminary differential item functioning analyses and outcome measurement analyses provided evidence for the tool?s generalisability and use as an outcome measure. Four themes resulted in Stage Two. The occupational therapists reported that the changes following the Rasch analysis have resulted in the tool being easier and more efficient to use in practice. However, there were issues residing in other sections of the tool that could not be remedied using Rasch analysis. Subsequently, additional refinements were made including re-branding as the Trinity Student Occupational Performance Profile (TSOPP), improving the face validity of other sections of the tool, and the development of an administration manual. Conclusion: The TSOPP is a valid and reliable self-report measure of occupational performance difficulties within the student role for students with disabilities in higher education.
APPROVED
Keywords: Rasch analysis; occupational performance; students with disabilities; third-level education; Person-Environment-Occupation model; validity; reliability; self-report assessment